Informing decision making on climate change and low carbon futures: Framing narratives around the United Kingdom's fifth carbon budget. (September 2017) - Howarth, Candice
Highlights: Narratives and stories can increase experiential engagement on climate change. Framing a low carbon future as positive and desirable enables better acceptance of the need to change. Six narratives are identified to engage audiences less inclined to want to engage with climate change. Narratives and storytelling on climate change go beyond the linear 'information deficit' model. Abstract: Narratives can help increase experiential engagement with climate change and build support for transitions to a low carbon future. The UK's 2050 climate targets provide indicatives frames through which emissions reductions could be translated to different contexts. The scenarios outlined in the UK's fifth carbon budget will require lifestyle changes which may need to counter low levels of acceptance of the need to change through technological, political and behavioural initiatives. This paper explores the role of narratives of the UK's fifth carbon budget in increasing engagement to climate change. Data are presented from thirty semi-structured interviews with UK academic, policy and practitioner communities. Six narratives are identified that could enable positive engagement with a low carbon future and better engagement on climate change: (i) showcasing investment opportunities; (ii) maintaining independence and freedom of choice; (iii) guiding audiences to visualise a low carbon future; (iv) demonstrating broader appeal, salience and impact of not doing anything; (v) supporting transitions and change; (vi) highlighting benefits to quality of life. Implications of these findings to public engagement on climate change and perceptions of how life may need to be reconfigured in a low carbon future are discussed.